Microfluidic arrays of dermal spheroids: a screening platform for active ingredients of skincare products. Issue 20 (31st August 2021) - Chen, Zhengkun; Kheiri, Sina; Gevorkian, Albert; Young, Edmond W. K.; Andre, Valerie; Deisenroth, Ted; Kumacheva, Eugenia
Abstract : A novel microfluidic array of a spheroid-based dermis model enables time-efficient in vitro screening of active ingredients of skincare products. Abstract : Organotypic micrometre-size 3D aggregates of skin cells (multicellular spheroids) have emerged as a promising in vitro model that can be utilized as an alternative of animal models to test active ingredients (AIs) of skincare products; however, a reliable dermal spheroid-based microfluidic (MF) model with a goal of in vitro AI screening is yet to be developed. Here, we report a MF platform for the growth of massive arrays of dermal fibroblast spheroids (DFSs) in a biomimetic hydrogel under close-to-physiological flow conditions and with the capability of screening AIs for skincare products. The DFSs formed after two days of on-chip culture and, in a case study, were used in a time-efficient manner for screening the effect of vitamin C on the synthesis of collagen type I and fibronectin. The computational simulation showed that the uptake of vitamin C was dominated by the advection flux. The results of screening the benchmark AI, vitamin C, proved that DFSs can serve as a reliable in vitro dermal model. The proposed DFS-based MF platform offers a high screening capacity for AIs of skincare products, as well as drug discovery and development in dermatology.